THE EFFECT OF DIVIDEND TAX LITERATION AND PERSONAL MOTIVATION ON BEHAVIOR INVESTORS IN INVESTORS PT CENTRAL CAPITAL FUTURE (PERSERO) - SE, Dimas Aditya (Jurnal Ilmiah Mahasiswa FEB, 2019)
This study aims to analyze the effect of taxation and personal motivation on investment, on the investors of PT Central Capital Future (Persero) Tbk.This type of research used in this research is quantitative research. Study method used is the research is explanatory research. In collecting data, the technique used is the distribution of questionnaires. Sample A total of 160 investors PT Central Capital Future (Persero) Tbk. The analytical tool used is multiple linear regression. Then to test the hypothesis used the F test and t test.The results of the multiple linear regression analysis show tax literacy and motivation on simultaneous and also partial investment policies. Then seen from the Adjusted R Square value of 0.560 which means that 56% of the investment influence variable (dependent variable) can be explained by the independent variables consisting of tax literacy and Individual Motivation. While 44% was accepted by other variables not discussed in this study. Keywords: Tax Literacy, Individual Motivation, Investment Behavior.